Lean Hospital Simulation Using The Value Stream Mapping (VSM) Method - Kuncorosidi, Kuncorosidi; Amelia, Rita; Apriandi, Devy Widya (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2023)
This study aims to analyze Lean Hospital simulations using the Value Stream Mapping (VSM) method at the Outpatient Unit at Mutiara Hati Hospital, Pagaden, Kab. Subang. This research was conducted to identify waste activities in the work process in the outpatient unit and to analyze the Value Stream Map of the outpatient unit.The observation method in this study uses descriptive quantitative methods. Observation, interviews, literature studies, field studies, and documentation carry out data collection techniques. The analysis technique used in this study used the Visio software version and CorelDraw.The research results on activities during the outpatient unit process found waste, so the PEC (process cycle efficiency) value was less than 30%. Proposed improvements using Lean Hospital to minimize waste or waste in outpatient units are carried out by reducing waiting time.Keywords: Lean Hospital; Value Stream Mapping (VSM).